The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2196/28020
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Behavior of Children with Profound Intellectual, Multiple, or Severe Motor Disabilities With Location and Environment Data Sensors for Independent Communication and Mobility: App Development and Pilot Testing

Abstract: Background Children with profound intellectual and multiple disabilities (PIMD) or severe motor and intellectual disabilities (SMID) only communicate through movements, vocalizations, body postures, muscle tensions, or facial expressions on a pre- or protosymbolic level. Yet, to the best of our knowledge, there are few systems developed to specifically aid in categorizing and interpreting behaviors of children with PIMD or SMID to facilitate independent communication and mobility. Further, environm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Their severe condition presents significant limitations in communication due to the inability to comprehend social cues, spoken, verbal or symbolic language [ 1 4 ]. These are often manifested in atypical, minute, and refined body and hand postures and movements, vocalizations and utterances, muscle tensions, or facial expressions on a presymbolic (nonsymbolic) or protosymbolic level with no shared meaning and stereotypical non-communicative behaviors [ 1 3 , 7 9 ]. Such extensive communication ambiguities impede expressing their needs, desires, thoughts, and feelings requiring great dependence on their close caregivers who are more capable of discerning and interpreting the most idiosyncratic behaviors than other people, thus limiting their communication group [ 2 , 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Their severe condition presents significant limitations in communication due to the inability to comprehend social cues, spoken, verbal or symbolic language [ 1 4 ]. These are often manifested in atypical, minute, and refined body and hand postures and movements, vocalizations and utterances, muscle tensions, or facial expressions on a presymbolic (nonsymbolic) or protosymbolic level with no shared meaning and stereotypical non-communicative behaviors [ 1 3 , 7 9 ]. Such extensive communication ambiguities impede expressing their needs, desires, thoughts, and feelings requiring great dependence on their close caregivers who are more capable of discerning and interpreting the most idiosyncratic behaviors than other people, thus limiting their communication group [ 2 , 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This entails two major steps, the first of which is the collection, extraction, and initial categorization of the movements of the children based on the interpretations of their caregivers. This was initially performed using a previously developed mobile app called ChildSIDE that enabled the collection of 327 behavior data from 20 children-caregiver dyads [ 9 ]. Video-based retrospective inter-rater agreement Kappa analyses revealed that most of the movements of children with PIMD/IDs were manifested mainly through body (27.7%; approaching, contacting, and movement of part of the body) and hand movements (22.8%; pointing, reaching, and moving).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations